JOSÉ PEDRO VARELA IN THE GESTATION OF THE URUGUYAN SCHOOL - Bralich, Jorge (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
We propose to emphasize the importance of Jose Pedro Varela in the Latin-American concert, as builder of the Uruguayan school system. This work summarizes long researches about the work and personality of Varela, these were done years before and synthetically expressed in our work “Varela “ (1989). The mentioned research was based on the re-reading of his writings their different contexts in the social, political and economic environment in which he lived. From it, it arose that the well-known image of Varela has been very schematic and it does not rescue the complexity of his personality. In effect Varela, an intelligent and dynamic young person inspired by the work of Sarmiento, together with several young friends stimulated the creation of an educational movement (the “ Friends’ Society of the Popular Education “) it came together in the approval - for the Government - of a Law of Education and in his designation as National Inspector of Public Instruction in 1877. His early death in 1879 did not prevent him from stopping laid the foundations of a school system, which general lines would extend across any more than one century. Though he has not been sufficiently recognized worldwide, in Uruguay - and in any measure, in the Rio de la Plata - it is one of the figures distinguished from the educational history